Development of capitals and capabilities of smallholder farmers for promoting inclusive intensification in agriculture: Experiences from northern West Bengal, India - Pulak Mishra; Bhagirath Behera; Niladri Sekhar Bagchi; Bidur Pariaare; V. Ratna Reddy; Chiranjeevi Tallapragada; Subrata Majumdar; Dil Bahadur Rahut (Asian Development Bank Institute (ADBI), 2023)
While policies and institutional arrangements aimed at intensification and growth of the Indian agriculture sector are inevitable for the livelihoods and food security of the country's vast population, the inclusion of land-constrained farmers especially women, therein requires certain fundamental changes in the approaches. Efforts toward such changes based on a deeper understanding of the underlying issues and dynamics seem to be more pertinent, particularly at the onset of various crises in the sector and measures undertaken by the government to address the same. This paper analyzes the experiences of interventions in two selected villages in West Bengal and the subsequent changes in farming practices by land-constrained farmers therein to design a framework aimed at strengthening the institutional approach. Using insights from focus group discussions, open interviews, field observations, and repeated engagement with the stakeholders, this paper argues that while collectivization of resources and actions can potentially lead to the inclusion of smallholder farmers and women in the intensification process, benefitting from the opportunities under the changing socioeconomic environment would require the development of the necessary capacities and capabilities of the farmers. Further, such capital formation and capability building through the process of ethical engagement with the community would also be crucial to overcome various constraints, particularly with regard to the scale of farming, market access, bargaining power, and risk-bearing ability. Nevertheless, continuation of the supporting incentives and related institutional reforms would be essential in this regard.
Keywords: Q1; O13; I3; H8; 330; institutions; policy; collectivization; smallholders; sustainability; agriculture; West Bengal; India